2018
DOI: 10.1007/978-3-319-99731-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Fano-resonances in High Index Dielectric Nanowires for Directional Scattering

Abstract: High refractive index dielectric nanostructures provide original optical properties thanks to the occurrence of size-and shape-dependent optical resonance modes. These modes commonly present a spectral overlap of broad, low-order modes (e.g. dipolar modes) and much narrower, higher-order modes. The latter are usually characterized by a rapidly varying frequency-dependent phase, which -in superposition with the lower order mode of approximately constant phase -leads to typical spectral features known as Fano re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…Following this, Yuan Hsing Fu et al observed the directional scattering behavior of silicon nanoparticles in the visible light range [19]. Later on, a series of work has been carried out to improve the directional scattering efficiency and its operation wavelengths by other mechanisms, such as the Fano resonance [18,20] and the multibody enhanced electric field [21].…”
Section: Introductionmentioning
confidence: 97%
“…Following this, Yuan Hsing Fu et al observed the directional scattering behavior of silicon nanoparticles in the visible light range [19]. Later on, a series of work has been carried out to improve the directional scattering efficiency and its operation wavelengths by other mechanisms, such as the Fano resonance [18,20] and the multibody enhanced electric field [21].…”
Section: Introductionmentioning
confidence: 97%
“…The impact of shape on resonant-optical absorption in semiconductor has been studied in great detail in literature [86]. This higher optical absorption of deformed particles can be associated with better coupling of light to resonance mode of deformed (rectangular) particles [86,87]. This observation suggests that the guidelines established in this work are applicable to particulate semiconductor photoanodes composed of non-spherical particles.…”
Section: Impact Of Particle Shapementioning
confidence: 70%
“…The deformed particle shows slightly higher optical absorption. The impact of shape on resonant-optical absorption in semiconductor has been studied in great detail in literature [86]. This higher optical absorption of deformed particles can be associated with better coupling of light to resonance mode of deformed (rectangular) particles [86,87].…”
Section: Impact Of Particle Shapementioning
confidence: 99%